Discourse Theory and Performance-Based Assessment: Two Tools for Professional Interpreting - Clifford, Andrew (Meta, 2001)
AbstractThis article examines interpreter assessment and draws attention to the limits of a lexico-semantic approach. It proposes using features of discourse theory to identify some of the competencies needed to interpret and suggests developing assessment instruments with the technical rigour common in other fields. The author gives examples of discursive features in interpretation and shows how these elements might be used to construct a rubric for assessing interpreter performance.